Transfer of aflatoxin M1 and sterigmatocystin from buffalo milk to soft cheeses - Maurizio Cossu; Andrea Sanna; Giannina Chessa; Stefano Sdogati; Ivan Pecorelli; Ilaria Di Marco Pisciottano; Sara Lambiase; Pasquale Gallo; Stefania Massafra; Elena Torres; Marilena Gili; Giovanni Lo Cascio; et al. (Revista Científica)
Aflatoxin M1 (AFM1) may be present in milk as a result of the ingestion of aflatoxin B1 (AFB1), which could potentially be contained in dairy feed due to contamination by molds such as Aspergillus flavus and A. parasiticus. AFM1 is a toxic molecule classified by the IARC as “potentially carcinogenic to humans” in Group 1. In addition to the four aflatoxins (AFB1, AFB2, AFG1, and AFG2), these fungi also produce other toxins such as Sterigmatocystin (STC), while Aflatoxicol (AFL) is a metabolite of AFB1. The aim of this study was to investigate the transfer of AFM1 and STC from naturally contaminated buffalo milk to soft cheeses. During routine activities carried out in the Lazio region (Italy) between July 2022 and May 2023, eight bulk buffalo milk samples, with AFM1 incidence, were found on eight different farms. Bulk milk samples were immediately collected to conduct eight experimental mini-cheese-making procedures, following the traditional production method of mozzarella and ricotta. These soft cheeses were manufactured, and samples of whey, and spinning water were collected. All samples were analysed for AFM1, AFL, and STC was determined with the LC-MS/MS system. The  concentrations in milk were: AFM1 range of 6-87 ng/kg; STC range of 0.3-0.8 ng/kg (detected in only five lots). AFL was never detected (LoQ>4 ng/kg). Mycotoxins detected in cheese were, for mozzarella, AFM1 concentration range of 15-233 ng/kg; STC concentration range of 0.9-10 ng/kg; while for ricotta, AFM1 concentration range 4.2-92 ng/kg and STC concentration range 0.5-4 ng/kg. AFL was never detected (LoQ>10 ng/kg). Interestingly, the range concentration of AFM1 in the spinning water was 1.2 – 21 ng/kg. Even though it is to a small extent, the processing technology, which uses hot water to spin the mozzarella, can act as a detoxifier. The assessment of the AFM1 enrichment factor (EF) in cheeses made with contaminated milk, revealed an EF of 2.4 for mozzarella and 1.2 for ricotta; EFs were calculated as the ratio (%) between AFM1 in the respective cheese and AFM1 in milk. In conclusion, the EFs found in our study are similar to those reported in the literature for these cheeses, and below the suggested value proposed by the Italian Ministry of Health of 3.0 for soft cheese like mozzarella and ricotta. Among the other toxins analysed, only STC was found, although in low concentrations, while AFL was never detected.